Feasibility of intranasal versus subcutaneous drug administration: a non-randomised crossover study - Hirschinger, Hanna; Rémi, Constanze; Thanbichler, Eric; Hofmann, Wolf-Karsten; Gencer, Deniz; Boch, Tobias (American journal of hospice & palliative medicine, 2026)
Background - In palliative care, drug delivery methods must be simple, rapid and acceptable especially in homecare settings to relatives as non-professional caregivers. This study compared intranasal (IN) and subcutaneous (SC) administration performed by medical laypersons under standardized conditions. - Methods - 31 volunteers without medical training participated in a non-randomised crossover study. After receiving instructions, participants performed both SC and IN administration in a simulated environment using placebo medication. Primary endpoints were preparation and administration time. Secondary endpoints included perceived ease, comfort, safety and handling difficulties. Data were collected using structured questionnaires. Statistical analyses used paired t-tests and binomial testing. - Results - All participants (27 female, median age range 50-60 years) completed both procedures. Mean administration time: 4:49 minutes (SD 1:20) for SC, 1:16 minutes (SD 0:20) for IN (p < .001, d = 2.97). >90% preferred IN and rated it as easier (30/31, 97%), more comfortable (30/31, 97%), faster (30/31, 97%) and safer (21/31, 68%). SC was consistently rated more complex (30/31, 97%) and cumbersome (30/31, 97%). Handling errors were more frequent with SC application. Nearly half of participants (15/31) had prior SC experience, while all had personal experience with nasal sprays, though not in administering them to another adult. Participants emphasized the importance of training for safe and accurate administration. - Conclusion - Medical laypersons strongly preferred IN over SC administration. IN was significantly faster, more acceptable and associated with fewer handling problems. These findings support IN administration as a practical and caregiver-friendly alternative in palliative care. - Clinical Trial Number - Not applicable. - Trial Identification - 173-02, protocol Version 02, 03.11.2022.